Distance learning and student motivation reinforcement during the COVID-19 pandemic through KKN Tematik UPI program - Fatoni, Agus; Masharyono, M. (Universitas Pendidikan Indonesia, 2023)
During the COVID-19 pandemic, the government decided to stop activities at schools. Students are forced to carry out learning activities boldly. In distance learning, several obstacles must be identified, and solutions sought. This service aims to help teachers, students, and parents deal with problems arising from implementing distance learning. One way to organize community service activities is KKN in the field of education at SDN Pancasila Lembang. The service method strengthens distance learning by selecting suitable learning media for students. Also, the implementation of talk show activities with the theme of growing student learning motivation to achieve goals. This activity is carried out to make it easy for students to carry out distance learning activities while remaining enthusiastic to reach their goals. The findings from the KKN program activities are that teachers and parents perceive positively related to the implementation of the entire program. Teachers and parents were satisfied with the series of actions that had been prepared and found it helpful to find new ways and perspectives. Also, activity programs make student learning experiences more effective and increase student motivation.